2007
DOI: 10.2146/ajhp070063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacy practice residency training on residents’ knowledge of and interest in clinical research

Abstract: Although there was improvement from the beginning to the end of residency in subjectively assessed research-related skills and abilities and in self-assessed understanding of most statistical tests, the end of residency objectively assessed research-related knowledge scores were unchanged. Residents' expectations that the residency would increase research knowledge, skills, and desire for research involvement were unmet. These results suggest that training based on residency program standards may not increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 13 publications
2
68
1
2
Order By: Relevance
“…Most of our respondents had completed a residency, and few (<15%) had completed a fellowship. With the lack of appropriate research training provided at residencies, 10 it is uncertain how successful junior faculty members will be in conducting research activities. Post-doctoral training in the form of a fellowship, master's or PhD programs, appear to be more appropriate for obtaining research training; however, there is concern for the length of time required to complete these programs that may dissuade pharmacists from pursuing these options.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our respondents had completed a residency, and few (<15%) had completed a fellowship. With the lack of appropriate research training provided at residencies, 10 it is uncertain how successful junior faculty members will be in conducting research activities. Post-doctoral training in the form of a fellowship, master's or PhD programs, appear to be more appropriate for obtaining research training; however, there is concern for the length of time required to complete these programs that may dissuade pharmacists from pursuing these options.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into pharmacy residents' knowledge about research and biostatistics have found disappointing results. 2,3 This knowledge deficit unfortunately extends to practicing pharmacists as well. 4 This gap in knowledge by residents and preceptors likely in part contributes to the single-digit publication rates of pharmacy residency projects.…”
mentioning
confidence: 99%
“…1 Factors associated with this shortage include the increasing number of pharmacy schools, and lack of teaching experience and research exposure among residents, resulting in lack of interest in a career in academia. [2][3][4][5] Research articles have examined teaching experiences and variables that influence a pharmacy resident's interest for academic faculty positions. [2][3][4] Sheaffer and colleagues identified predictors associated among first-year pharmacy residents (PGY1s) with academic career choices.…”
mentioning
confidence: 99%
“…4 In summary, authors have identified the need to increase teaching exposure and increase academic-based training in order to increase residents' preparedness to pursue faculty positions, and potentially alleviate the faculty shortage. [2][3][4][5] Loma Linda University School of Pharmacy (LLUSP) recognized the difficulty in recruiting qualified faculty candidates, so in an effort to address this issue, a pharmacy practice residency program (PGY1) with an emphasis in academia was implemented. The LLUSP PGY1 program (ASHP-accredited) consists of clinical requirements (75%) and academic requirements (25%) upon completion.…”
mentioning
confidence: 99%
See 1 more Smart Citation